Germinação e vigor de sementes de Mimosa caesalpiniifolia Benth. sob estresse hídrico e salino - Sousa, Eduardo Chaves de (2017)
Mimosa caesalpiniifolia Benth., known by sabiá in the brazilian Northeast, is a forest species native to the Caatinga and belonging to the Fabaceae family. It has recently been included in the list of vulnerable species due to their use as wood, firewood and charcoal. Seeds of species that develop in soils of arid and semi-arid regions, such as sabiá, commonly find unsuitable conditions for germination, such as soils affected by water deficiency and abundance of saline soils. The objective of this study was to evaluate the effect of water and saline stress on the germination and seed vigor of three lots of M. caesalpiniifolia from matrices located in the municipalities of Luziania - GO (Lot 1), Vazante - MG (Lot 2) and Mountains - RN (Lot 3). In the simulation of the water restriction, two osmotic agents, mannitol and polyethylene glycol 6000 (PEG 6000), adjusted for the osmotic potentials of 0; -0.2; -0.4; -0.6 and -0.8 MPa. To simulate salt stress, NaCl solutions were used in the electrical conductivities of 0,0; 5.0; 10.0; 15.0; 20.0; 25.0; 30.0 dS m-1. Were analyzed: germination, germination velocity index, shoot and root length and dry mass of shoot and root of seedlings. The experimental design was completely randomized, with four replicates of 25 seeds for each treatment. The results demonstrated that mannitol-induced water stress did not influence seed germination and root length of sage seedlings, reduced IVG and seedlings dry length and dry mass, and increased dry mass of seedlings. The water restriction simulated with PEG, in turn, was more critical, reducing percentage and speed of germination, aerial and root length, as well as dry mass of shoot and root of seedlings. The three batches responded similarly to water stress, but Lot 3, with seeds from Montanhas – RN, was less vigorous than the others. The salinity reduced the germination and vigor of M. caesalpiniifolia seeds, reducing the parameters evaluated in the higher electrical conductivities (25.0 and 30.0 dS m-1), and affecting in a more expressive way, IVG and length of seedlings. Lot 2 was more tolerant of salt stress